Introducing labour productivity changes into models used for economic impact analysis in tourism. Issue 3 (May 2017) - Klijs, Jeroen; Peerlings, Jack; Heijman, Wim
In tourism management, traditional input–output models are often applied to calculate economic impacts, including employment impacts. These models imply that increases in output are translated into proportional increases in labour, indicating constant labour productivity. In non-linear input–output (NLIO) models, final demand changes lead to substitution. This causes changes in labour productivity, even though one unit of labour ceteris paribus still produces the same output. Final demand changes can, however, also lead to employees working longer, harder and/or more efficiently. The goal of this article is to include this type of 'real' labour productivity change into an NLIO model. To do this, the authors introduce factor augmenting technical change (FATC) and a differentiation between core and peripheral labour. An NLIO model with and without FATC is used to calculate the regional economic impacts of a 10% final demand increase in tourism in the province of Zeeland in the Netherlands. Accounting for real productivity changes leads to smaller increase in the use of labour, as productivity increases allow output to be produced using fewer inputs.